Haemodialysis adequacy – contemporary trends - Zyga, Sofia; Sarafis, Pavlos (My University, 2009)
Haemodialysis constitutes a prescribed clinical action, a fact which leads us to the search of indexes that control the adequacy of haemodialysis and to a more precise estimation of the intended and the performed result. Objective: The purpose of this literature review was to present the quantitative and mathematical indexes used for the calculation of the haemodialysis adequacy in the daily clinical practice. Method and material: The method οf this study included bibliography research from both the review and the research literature which carried out mainly internationally over the last years and referred to haemodialysis adequacy. Results: In daily clinical practice, useful tools for the calculation of haemodialysis adequacy are the indexes Urea Reduction Rate (URR), single-pool Kt/V (spKt/V) index, equilibrated Kt/V (eKt/V) index and weekly standard Kt/V (std Kt/V) index. The knowledge of factors that influence the urea clearance within treatment and can offer important help to the successful haemodialysis prescription, are: blood flow, filter permeability, haemodialysis dialysate flow and recirculation. Clinical indexes are may also be considered for a more effective haemodialysis process: good natural health, good regulation of arterial pressure, good regulation of liquids balance and absence of clinical points or uraemia symptoms. Conclusions: The main conclusion of the present review is to apply the indexes in daily clinical practice. Moreover, it is important to set out certain proposals for further research, so that the health professionals improve not only the clinical practice but also the theoretical approach in the field of determination and estimation of haemodialysis adequacy.
Keywords: Adequacy; Haemodialysis; Kt/V index; Nursing; Uraemia